2019
DOI: 10.3390/ijms20030564
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and Signaling Pathways Response to Dry Needling Combined with Static Stretching Treatment for Chronic Myofascial Pain in a RAT Model: An Explorative Proteomic Study

Abstract: A quantitative proteomic analysis of the response to dry needling combined with static stretching treatment was performed in a rat model of active myofascial trigger points (MTrPs). 36 rats were divided into a model group (MG), a stretching group (SG) and a dry needling combined with stretching group (SDG). We performed three biological replicates to compare large-scale differential protein expression between groups by tandem mass tag (TMT) labeling technology based on nanoscale liquid chromatography mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…Recently, studies based on proteomics have proposed an increase in specific proteins after dry needling, including actinin alpha 3, calsequestrin-1, parvalbumin alpha, pyruvate kinase muscle isoenzyme (PKM), muscle isoform of glycogen phosphorylase (PYGM) and myozenine 2 (MYOZ2), which may reinforce the hypothesis that increased local blood supply plays a major role in the therapeutic effects of dry needling. 40,41 Our results did not demonstrate significant effects on edema or thermography. We would consider the methods we used to evaluate thermal and mechanical hyperalgesia a limitation of this study, as myofascial pain may be more related to sensitization of deep nociceptors, and not as much to nociceptors in the skin or other superficial tissue, 42 although this hypothesis may directly contradict the responses found in a study by DeSantana and Sluka, 32 in which the same evaluation method positively detected superficial hyperalgesia.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Recently, studies based on proteomics have proposed an increase in specific proteins after dry needling, including actinin alpha 3, calsequestrin-1, parvalbumin alpha, pyruvate kinase muscle isoenzyme (PKM), muscle isoform of glycogen phosphorylase (PYGM) and myozenine 2 (MYOZ2), which may reinforce the hypothesis that increased local blood supply plays a major role in the therapeutic effects of dry needling. 40,41 Our results did not demonstrate significant effects on edema or thermography. We would consider the methods we used to evaluate thermal and mechanical hyperalgesia a limitation of this study, as myofascial pain may be more related to sensitization of deep nociceptors, and not as much to nociceptors in the skin or other superficial tissue, 42 although this hypothesis may directly contradict the responses found in a study by DeSantana and Sluka, 32 in which the same evaluation method positively detected superficial hyperalgesia.…”
Section: Discussioncontrasting
confidence: 63%
“…Recently, studies based on proteomics have proposed an increase in specific proteins after dry needling, including actinin alpha 3, calsequestrin-1, parvalbumin alpha, pyruvate kinase muscle isoenzyme (PKM), muscle isoform of glycogen phosphorylase (PYGM) and myozenine 2 (MYOZ2), which may reinforce the hypothesis that increased local blood supply plays a major role in the therapeutic effects of dry needling. 40,41…”
Section: Discussionmentioning
confidence: 99%
“…This is beginning to change, however, as we are seeing the emergence of new magnetic resonance elastography methods, as well as a rodent model of myofascial trigger points combining a soft tissue injury with repeated bouts of exercise. 13,40 What role "myofascial" tissues play in chronic musculoskeletal back pain is clearly a substantial gap area in need of more research. 31…”
Section: Pain and The Brainmentioning
confidence: 99%
“…8,9,16 There is also evidence that acupuncture needling mechanically engages connective tissue and may have local effects similar to manual therapies, as well as "deactivate" myofascial trigger points by eliciting a characteristic twitch response. 37,40,71 Additionally, the sensory input produced during acupuncture needling seems to have many neuro-affective effects in common with those of mind-based treatments, including descending pain inhibition and activation of pain matrix brain areas. 33 Mind and body therapies such as yoga and tai chi potentially combine all 3 types of beneficial effects: enhanced descending pain inhibition, behaviorally mediated improvement in movement patterns, and direct stretching of tissues.…”
Section: Mind and Body Approaches To Chronic Musculoskeletal Painmentioning
confidence: 99%
“…Muscle stretching techniques are suggested for relaxation of the trigger points (Hanten, 2000, Ma, 2010 because of the stretching exercises helps to overcome the energy crisis within a trigger point (Gerwin, 2005). A large number of studies have confirmed the beneficial effects of skeletal muscle stretching on muscle performance, range of motion and even neurological responses (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%